2018
DOI: 10.1016/j.bioelechem.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the anode potential on the physiology and proteome of Shewanella oneidensis MR-1

Abstract: Shewanella species respire using iron and manganese oxides as well as electrodes as solid terminal electron acceptors. Shewanella oneidenis MR-1 exploits mediated as well as direct extracellular electron transfer (EET) modes to transfer electrons at different formal potentials. These different EET modes at different potentials may utilise alternate electron transfer pathways. Therefore, we investigated how different anode potentials, providing different maximum microbial energy gains impacted S. oneidensis mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…oneidensis MR-1 cells to the electrodes. All the pure EMs showed clear redox peaks (red line), while the EMs with biofilm revealed a sigmoidal anodic current profile characteristic of catalytic activity (black line). This positive current was observed above a potential of mid-potential of EMs, reflecting the flow of electrons from bacteria to electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…oneidensis MR-1 cells to the electrodes. All the pure EMs showed clear redox peaks (red line), while the EMs with biofilm revealed a sigmoidal anodic current profile characteristic of catalytic activity (black line). This positive current was observed above a potential of mid-potential of EMs, reflecting the flow of electrons from bacteria to electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…The data (Figure 2a) showed that, while the peak oxidative current of biofilm without EMs was very low (black line, 0.05 mA), much higher currents (1−3 mA) were observed in all the BESs with EMs (Figure 2b−f), indicating that the redox cycling of EMs should have a comparatively high contribution to the overall electron flux from S. oneidensis MR-1 cells to the electrodes. All the pure EMs showed clear redox peaks (red line), while the EMs with biofilm revealed a sigmoidal anodic current profile characteristic 58 of catalytic activity (black line). This positive current was observed above a potential of mid-potential of EMs, reflecting the flow of electrons from bacteria to electrodes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With regard to the cathodic electrons used for acetate production, hydrogen evolution and Cd(II) removal, it is difficult to exactly quantify the amounts of electrons used by each product. Although, electron acceptors (HCO3 -, H + , or Cd(II)) are beneficial for the electron transfer process from the cathode [46], it has yet to be demonstrated that electron transfer to these species are also associated to cell respiration. In fact there are a variety of other possible mechanisms by which bacterial cells might catalyze the reduction of Cd(II), and the production of acetate and hydrogen [47].…”
Section: Impact Of Cd(ii) Concentrationmentioning
confidence: 99%
“…Se realizó por triplicado [17]. como sustrato [19], así como también al enriquecimiento con microbio electroactívo en el ánodo y a las transferencias de electrones o a la autorregulación de las vías extracelulares de 60 transferencia de electrones [20][21][22]. El descenso de los valores de voltaje y corriente en los últimos días se debería a la difusión de oxígeno del cátodo al ánodo debido a la falta de una membrana entre ellos [23].…”
Section: B Aislamiento De Levaduraunclassified